Perspectives of herbs and their natural compounds, and herb formulas on treating diverse diseases through regulating complicated JAK/STAT signaling - Jian-Yu Chen; Xiao-Yun Tian; Shan-Shan Wei; Ying-Jie Yang; Shan Deng; Chun-Jie Jiao; Can-Jian Wang; Ke-Dan Chu; Xue-Qin Ma; Wei Xu (Frontiers Media S.A., 2022)
JAK/STAT signaling pathways are closely associated with multiple biological processes involved in cell proliferation, apoptosis, inflammation, differentiation, immune response, and epigenetics. Abnormal activation of the STAT pathway can contribute to disease progressions under various conditions. Moreover, tofacitinib and baricitinib as the JAK/STAT inhibitors have been recently approved by the FDA for rheumatology disease treatment. Therefore, influences on the STAT signaling pathway have potential and perspective approaches for diverse diseases. Chinese herbs in traditional Chinese medicine (TCM), which are widespread throughout China, are the gold resources of China and have been extensively used for treating multiple diseases for thousands of years. However, Chinese herbs and herb formulas are characterized by complicated components, resulting in various targets and pathways in treating diseases, which limits their approval and applications. With the development of chemistry and pharmacology, active ingredients of TCM and herbs and underlying mechanisms have been further identified and confirmed by pharmacists and chemists, which improved, to some extent, awkward limitations, approval, and applications regarding TCM and herbs. In this review, we summarized various herbs, herb formulas, natural compounds, and phytochemicals isolated from herbs that have the potential for regulating multiple biological processes via modulation of the JAK/STAT signaling pathway based on the published work. Our study will provide support for revealing TCM, their active compounds that treat diseases, and the underlying mechanism, further improving the rapid spread of TCM to the world.